High-Quality Outdoor Learning Evidence-based Education Outside the Classroom for Children, Teachers and Society - Jucker, Rolf; von Au, Jakob (Springer Nature, 2022)
This open access book reviews evidence and case studies on the effects of outdoor learning on teachers and learners. It shows how real-world learning outside the classroom contributes to unlocking the full potential of learners, demonstrating its benefits for academic learning, social competencies, personal and emotional development, psychological well-being, and physical activity and health. In addition, the book highlights how outdoor learning nurtures environmental awareness and helps learners to tackle current sustainability challenges. Its focus on high-quality learning makes it a unique contribution to the implementation of SDG 4. Aimed at lecturers at teacher training universities, teachers, professional educators, coaches, and multipliers who train staff of educational NGOs, as well as decision makers on all levels of education systems, this book is of interest to all those who seek a more in-depth understanding of the future of education.